Parents and Children's Perceptions of Online Learning During the Covid-19 Pandemic in East Alok District - Indrayani, Fitria (EduMatika: Jurnal MIPA, 2022)
The purpose of this study is to know the perception of parents and children about learning online during Pandemi Covid-19 in East Alok District. This research was conducted in Nangameting Village. RT 002 and Waioti Village RT 038 Alok Timur District. This study uses data collection techniques, descriptive qualitative methods with interview techniques with 68 respondents. The results of the interview of parents and children reveal that online learning is felt ineffective, namely children bored, the performance of children is affected, children do not understand the task, and material is inadequate. For reasons such as given by the teacher, children play and children who are not focused. In addition, parents must also accompany children in online learning. This was also stated by children who felt online learning was ineffective because they felt difficulties in understanding the material and tasks given by their teachers during the online learning process. Cannot meet directly with the teacher, too many tasks, and lack of knowledge about how to use applications. Obstacles between parents and children in online learning, internet quota used by children to play, Android phones do not exist, children do not understand material and tasks, limited economy, expensive quota, limited parental education, unstable networks, and do not understand how to use application